Trickle irrigation with nitrogen and potassium in tomato - Oliveira, Carlos A.S.; Carrijo, Osmar A.; Olitta, Antonio F.L.; Reis, Neville V.B. dos; Fontes, Ruy R. (Pesquisa Agropecuaria Brasileira, 2014)
Two levels of nitrogen and potassium were combined with drip irrigation system under edaphoclimatic conditions of "cerrado" soil in central Brazil to test their effect on the yield of 'Kada' tomato (Lycopersicum esculentum Mill). The water head was of 0.8, 1.0 and 1.2 levels of the class A evaporation tank settled on bare soil. Results showed no significant difference among treatments for the total fruit production per hectare. On the other hand, production of large fruits was different among treatments. It was observed that higher level of ammonium sulfate increased number and weight of fruits showing "blossom end rot", independently of the water head used. The combination of 0.8 water level with 1.400 kg/ha of ammonium sulfate and 918 kg/ha of potassium cloride proved to be the most effective in water utilization.